Evaluation of Antidiarrheal Activity of Methanolic Extract of Maranta arundinacea Linn. Leaves - Md. Khalilur Rahman; Md. Ashraf Uddin Chowdhury; Mohammed Taufiqual Islam; Md. Anisuzzaman Chowdhury; Muhammad Erfan Uddin; Chandra Datta Sumi (Hindawi Limited, 2015)
Diarrhea is one of the most common causes for thousands of deaths every year. Therefore, identification of new source of antidiarrheal drugs becomes one of the most prominent focuses in modern research. Our aim was to investigate the antidiarrheal and cytotoxic activities of methanolic extract of Maranta arundinacea linn. (MEMA) leaves in rats and brine shrimp, respectively. Antidiarrheal effect was evaluated by using castor oil-induced diarrhea, enteropooling, and gastrointestinal motility tests at 200 mg/kg and 400 mg/kg body weight in rats where the cytotoxic activity was justified using brine shrimp lethality bioassay at different concentrations of MEMA. The extract showed considerable antidiarrheal effect by inhibiting 42.67% and 57.75% of diarrheal episode at the doses of 200 and 400 mg/kg, respectively. MEMA also significantly p<0.01 reduced the castor oil-induced intestinal volume (2.14 ± 0.16 to 1.61 ± 0.12 mL) in enteropooling test as well as intestinal transit (33.00 to 43.36%) in GI motility test, compared to their respective control. These observed effects are comparable to that of standard drug loperamide (5 mg/kg). On the other hand, in brine shrimp lethality test after 24 h, surviving brine shrimp larvae were counted and LD50 was assessed. Result showed that MEMA was potent against brine shrimp with LD50 value of 420 µg/mL. So the highest dose of 400 µg/mL of MEMA was not toxic to mice. So these results indicate that bioactive compounds are present in methanolic extract of Maranta arundinacea leaves including significant antidiarrheal activity and could be accounted for pharmacological effects.